Pendampingan Kegiatan Community Service SMA Sukma Bangsa Bireuen di SDN 12 Juli Bireuen - Saputra, Nizar; Meutia, Hijriati; Al Dilwan, Muhammad (Nawadeepa: Jurnal Pengabdian Masyarakat, 2023)
This mentoring assistance aims to help third-year students of Sekolah Sukma Bangsa Bireuen to conduct proper community service to enhance their social well-being. The setting of community service was held in SDN 12 Juli Bivak in Bireuen regency. SDN 12 July is one of the elementary schools in the Bireuen regency that was located in a remote area in that regency. Due to its location, the school experiences a lack of school resources and students' learning motivation. The implication of this mentoring activity was to help the school to tackle and ease this problem. This mentoring activity was framed into three main stages including preliminary visits, planning, and community services. The result of this community service mentoring was to increase Students' learning motivation in SDN 12 Juli, improve school resources, and increase Sukma Bangsa Students’ social well-being.